Assessing and recovering Alzheimer’s disease: a comparative analysis of standard neuropsychological approaches and virtual reality interventions with the use of digital storytelling - Stasolla, Fabrizio; Di Gioia, Mariacarla; Messina, Irene; Treglia, Francesco; Passaro, Anna; Zullo, Antonio; Dragone, Mirella (Frontiers in Psychology, 2024)
Background Alzheimer’s disease (AD), the most common form of dementia, is a progressive neurodegenerative disorder that predominantly affects the elderly population. Traditional assessment methods, including neuropsychological tests like the MMSE, have been the cornerstone of AD diagnosis for decades. These methods are grounded in a wealth of research and clinical experience, providing a robust framework for understanding the cognitive deficits of AD. The evolution of AD assessment and rehabilitation has recently been tackled with the introduction of Virtual Reality (VR) technologies. Objectives To evaluate the use of storytelling and reminiscence therapy in virtual reality programs as a complementary and enhancing modality alongside standard assessment and rehabilitation for Alzheimer’s patients. To explore how regular interaction with VR narratives can slow cognitive decline or improve relevant features of cognitive functioning over the time. To propose a new assessment and rehabilitative tool based on the use of VR and digital storytelling. Method A comparative analysis of Standard Neuropsychological Approaches and Virtual Reality Interventions in patients with Alzheimer disorder was carried out. A literature overview on the empirical studies between 2019 and 2024 was conducted. Results We propose a new VR-based setup mediated by the use of storytelling for the assessment and recovery of AD. Conclusion The employment of storytelling within VR programs for the assessment and rehabilitation of Alzheimer’s disease can positively impact both the cognitive and emotional realms of patients, with beneficial outcomes on caregivers’ and families’ burden. The successful implementation of this approach requires careful consideration of accessibility, data interpretation, and standard validation protocols.